DEVELOPING OF ENGLISH INSTRUCTIONAL DESIGN FOR ENGLISH FOR SPECIFIC PURPOSE IN THE ISLAMIC RELIGIOUS EDUCATION STUDY PROGRAM - Situmorang, Khairani Hayat (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
ABSTRACTThe aim of this research is to produce teaching materials or Instructional Design for English courses in the Islamic Religious Education Study Program with the concepts of Contextual Teaching Learning and English for Specific Purposes with an orientation towards Student Learning Motivation based on aspects of validity, practicality and effectiveness. The research approach used is development research with the ADDIE development model. The test subjects in this research were fifth semester students in the Islamic Religious Education study program at the Daar Al Uluum Asahan Islamic Institute. The output in this research is a module for teaching English.Keywords: Instructional Design; English for Specific Purposes; Â Islamic education